Odpowiedzi

Najlepsza Odpowiedź!
2010-01-05T18:40:59+01:00
0,25x+0,4=0,35
0,25x=0,34-0,4
0,25x=-0,06 /:(0,25)
x=-0,24

2x-(3x+1)=6
2x-3x-1=6
-x=6+1
-x=7 /*(-1)
x=-7

2x-¾=½+x
2x-x=½+¾
x=²/₄+¾
x=⁵/₄
x=1¼

-0,2(5x-3)≥x-0,1
-x+0,6-x≥-0,1
-2x≥-0,1-0,6
-2x≥-0,7 /:(-2)
x≤ 0,35

(3x-2)²=9x+4
9x²-12x+4=9x+4
9x²-12x-9x=0
9x²-21x=0
3x(3x-7)=0
3x=0
x=0

3x-7=0
3x=7 /:3
x=⁷/₃
x=2⅓

(x-4)*(x+4)=x² -2x
x²-16=x²-2x
x²-x²+2x=16
2x=16 /:2
x=8
2010-01-05T18:56:45+01:00
1)0,25x+0,4=0,35
0,25=0,35 - 0,4
0,25= -0,05 /:0,25
x= 0,2

2)
2x-(3x+1)=6
2x-3x - 1=6
2x-3x=6+1
-1x=7 /:(-1)
x = -7

3)-0,2(5x-3) większe lub równe x-0,1
-1x + 0,6 większe lub równe x - 0,1
-1x -1x większe lub równe -0,1 - 0,6
-2x większe lub równe - 0,7 /:(-2)
x większe lub równe 0,35

4) (3x-2)do potęgi 2=9x+4
9x+ 4= 9x +4
9x - 9x= 4-4
0x = 0

5)(x-4)*(x+4)=x do potęgi 2 -2x